On the issues of auditing cryptographic applications and studying mono-unary algebras - Carrillo Ugalde, Jorge (2007)
In this thesis several applications of mono-unary algebras and a systematic approach to audit cryptographic applications were presented. This thesis is based on the observation that most of the procedures to perform IS audits utilize check-lists, which might not be applicable to all IT environments; however, by examining some applications of a simple algebraic structure, such as mono-unary algebras, a systematic methodology to execute an IS audit could be designed to improve the current IS audit approach. By defining basic components of an IS audit and simple relationships among them, one could create an efficient IS audit. It is not the aim of this thesis to provide a pure algebraic process to perform an IS audit; however, understanding several applications of mono-unary algebras can help to identify and abstract the basic elements of an IS audit. The main application of mono-unary algebras refers to the construction of the subgroupoid generated by a subset of the carrier of a fini.